STRATEGY OF WATER-FLOODING ENHANCEMENT FOR LOW-PERMEABLE POLYMICTIC RESERVOIRS - Palyanitsina , Aleksandra; Tananykhin , Dmitry; Masoud, Riazi (Journal of Applied Engineering Science, 2020)
This article pays attention to the issues of increasing the efficiency of the development of oil fields with low-permeable polymictic reservoirs. It is possible to increase the efficiency of this process by improving the technology of their artificial water-flooding. This goal is being realized by identifying the features of the development of low-permeable polymictic reservoirs of fields in Western Siberia and creating a strategy to improve the technology of artificial waterflooding, taking into account the impact on the surface molecular properties of the reservoir system by the stages of their development. The developed strategy was substantiated in stages using hydrodynamic modeling. Also, an assessment was made of the effectiveness of the implementation of low-salinity waterflooding at the late stage of development of low-permeability polymictic reservoirs, the optimal time for changing the waterflooding agent from formation water to fresh water was determined.